The impact of COVID-19 pandemic on pet behavior and human-animal interaction: a longitudinal survey-based study in the United States - Weng, Hsin-Yi; Ogata, Niwako (Frontiers in Veterinary Science, 2023)
Although multiple studies have explored behavioral changes in pets during the strict lockdown of the COVID-19 pandemic between May and July 2020, this longitudinal study uniquely investigated the phases beyond strict lockdown. The primary objective of this research was to evaluate the pandemic's impact on pet behavior. To achieve this goal, we conducted an online survey, completed by pet owners residing in the United States between June 2020 (including retrospective data for February and April 2020) and December 2021. The study encompassed four distinct pandemic phases: Pre-pandemic (data collected retrospectively), Strict lockdown, Prolonged lockdown, and Re-opening. The data collected from surveys completed by 3278 pet owners across one to six time points revealed declining trends in all investigated behavior problems of both dogs and cats. Concurrently, human-animal interaction activities also showed variations across different COVID-19 phases. The association between human-animal interactions and the occurrence of behavior problems underscored the importance of not only exercise quantity but also adherence to consistent schedules, particularly for dogs, in mitigating behavior problems. Interestingly, among cats, sleeping outside the bedroom was associated with a reduced occurrence of aggression, anxiety, fear, and physiological behavior changes. However, sleep location displayed limited or no association with behavior problems in dogs. In summary, this study highlights the importance of tailoring interventions to the unique needs of each species through human-animal interactions to mitigate the occurrence of behavioral problems and enhance human-animal relationships.